PENGARUH E-SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI INTERVENING PADA APLIKASI SHOPEE - Alexander Bryant Augustien (Jurnal Strategi Pemasaran, 2020)
This research aims to analyze the influence of electronic service quality (e-service quality) that affects loyalitas konsumen (customer loyalty) through customer satisfaction (customer satisfaction) on shopee application. The study used 170 respondents and processed by SEM-PLS method. results obtained by e-service quality affect customer loyalty with customer satisfaction as mediation